Potent and rapid activation of tropomyosin-receptor kinase A in endometrial stromal fibroblasts by seminal plasma†. Issue 2 (6th March 2018) - Martin, Jeremy W; Chen, Joseph C; Neidleman, Jason; Tatsumi, Keiji; Hu, James; Giudice, Linda C; Greene, Warner C; Roan, Nadia R
Abstract: Seminal plasma (SP), the liquid fraction of semen, is not mandatory for conception, but clinical studies suggest that SP improves implantation rates. Prior in vitro studies examining the effects of SP on the endometrium, the site of implantation, surprisingly revealed that SP induces transcriptional profiles associated with neurogenesis. We investigated the presence and activity of neurogenesis pathways in the endometrium, focusing on TrkA, one of the canonical receptors associated with neurotrophic signaling. We demonstrate that TrkA is expressed in the endometrium. To determine if SP activates TrkA signaling, we isolated the two most abundant endometrial cell types—endometrial epithelial cells (eEC) and endometrial stromal fibroblasts (eSF)—and examined TrkA activity in these cells after SP exposure. While SP only moderately activated TrkA in eEC, it potently and rapidly activated TrkA in eSF. This activation occurred in both non-decidualized and decidualized eSF. Blocking this pathway resulted in dysregulation of SP-induced cytokine production by eSF. Surprisingly, while the canonical TrkA agonist nerve growth factor was detected in SP, TrkA activation was principally induced by a 30–100-kDa protein whose identity remains to be established. Our results show that TrkA signaling is highly active in eSF and is rapidly induced by SP. Abstract : TrkA signaling is highly active in endometrial stromal fibroblasts and is rapidly induced by seminal plasma.